2019
DOI: 10.3390/ijerph16183427
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress among Field Epidemiologists in Field Epidemiology Training Programs from the Public Health Sector

Abstract: Despite the high-demand work environment for field epidemiologists in field epidemiology training programs, little is known about their occupational stress. To identify occupational stress and its related factors, the occupational stress among trainees in field epidemiology training programs in Southeast Asia and Western Pacific regions from 2016 to 2018 was examined using six subscales: Role Overload, Role Insufficiency, Role Ambiguity, Role Boundary, Responsibility, and Physical Environment. Furthermore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…A recent study reported the burden of occupational stress on Role Overload and Physical Environment among field epidemiologists in Southeast Asia and Western Pacific Regions was 56% and 53%, respectively [16]. In the current study, there was less burden of occupational stress on Role Overload and Physical Environment.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…A recent study reported the burden of occupational stress on Role Overload and Physical Environment among field epidemiologists in Southeast Asia and Western Pacific Regions was 56% and 53%, respectively [16]. In the current study, there was less burden of occupational stress on Role Overload and Physical Environment.…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, recruitment from the military sector is still a viable option. A previous study demonstrated that university-affiliated field epidemiologists are associated with reducing certain subdomains of occupational stress [16]; therefore, to recruit from the university-affiliated, not from military-affiliated personnel, may be one of the possible options to run the Korean program of field epidemiologists. However, more studies are required to identify possible ways to reduce turnover intention among Korean field epidemiologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many countries struggle to retain eld epidemiologists due to occupational burnout or career path limitations. (7,31,38) Ryu's study on eld epidemiology occupational stress, suggests that burnout is a very real concern given the frontline nature of outbreak and emergency response, with half of their respondents having experienced it. 7Respondents reported low levels of training in emergency response topics, however they said they were con dent in their learnt emergency response skills and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…(6) Responsibility for applied epidemiology workforce development varies depending on the country, and may include academic institutions and departments of health. (7,8) Commonly, academic institutions offer Masters of Public Health and or Epidemiology, whilst Governments largely support the Field Epidemiology Training Programme (FETP) model. 7The FETP model is a 'learning through doing' training approach, (4,8,9) which aims to strengthen public health systems through strengthening capacity for outbreak detection and response, as well as improved disease surveillance systems for evidence based decision making.…”
Section: Introductionmentioning
confidence: 99%